Transesophageal pulmonary lobectomy with single transthoracic port assistance: study with survival assessment in a porcine model - Pinto, João Moreira (2012)
BACKGROUND AND STUDY AIMS: Thoracoscopic pulmonary lobectomy is being performed in an increasing number of patients. The aims of the current study were to assess natural orifice transluminal endoscopic surgery (NOTES) as an alternative to transthoracic endoscopic surgery, and to test the feasibility of peroral transesophageal right upper pulmonary lobectomy with the assistance of a single transthoracic trocar. METHODS: In 10 acute and 4 survival pigs, right upper pulmonary lobectomy was performed using a forward-viewing double-channel gastroscope and an operative thoracoscope with a 5-mm working channel inserted through a single transthoracic 12-mm) port. Time, safety, and feasibility of the following steps were recorded in all animals: esophagotomy, hilar dissection, individual ligation of the hilum elements, pulmonary lobectomy, and specimen retrieval. In the survival experiments, esophagotomy was closed using a reticulated laparoscopy suture device and an esophageal stent was placed. These animals were kept alive and monitored for 2 weeks. RESULTS: Esophagotomy was performed safely in all animals (mean procedure duration 5.4 ± 1.7 minutes). Dissection of the right upper lobe hilum elements (bronchus, arteries, and veins) was carried out without adverse events. Individual ligation of the hilum elements was performed in all but two cases (time for dissection and ligation 44.2 ± 14.8 minutes). Lobectomy and specimen retrieval were completed in all animals (9.5 ± 3.1 minutes). Esophagotomy closure and stent placement were carried out in 20.0 ± 2.8 minutes in the survival animals. These animals fed normally and gained weight postoperatively without signs of disease. Endoscopic examination before necropsy revealed a pseudo-diverticulum in one animal, and wound dehiscence with confined collection/recess in the remaining animals. CONCLUSIONS: Transesophageal right upper pulmonary lobectomy using single transthoracic trocar assistance is feasible and may represent a step towards scar-free pulmonary lobectomy.